Estimating the ex ante Expected Returns to College - Hussey, Andrew J; Swinton, Omari H (American Economic Review, 2011)
Rather than estimating the returns to obtaining a college degree, this paper treats the college education decision as an uncertain investment involving varying likelihoods of successful graduation. We predict earnings conditional on both graduating and not graduating from both selective and non-selective institutions, and incorporate estimated individual-specific graduation rates in calculating the ex ante expected returns from college attendance for individuals across the ability distribution. Our results suggest that, especially for lower ability students, ex ante returns may differ substantially from typical estimates of the returns to a college degree, and typical estimates of the selectivity premium may be underestimated.